Violence and political theory - Frazer, Elizabeth (And political theory, 2020)
Is politics necessarily violent? Does the justifiability of violence depend on whether it is perpetrated to defend or upend the existing order – or perhaps on the way in which it is conducted? Is violence simply direct physical harm, or can it also be structural, symbolic, or epistemic? In this book, Elizabeth Frazer and Kimberley Hutchings explore how political theorists, from Niccolo Machiavelli to Elaine Scarry, have addressed these issues. They engage with both defenders and critics of violence in politics, analysing their diverse justificatory and rhetorical strategies in order to draw out the enduring themes of these debates. They show how political theorists have tended to evade the central difficulties raised by violence by either reducing it to a neutral tool or identifying it with something quite distinct, such as justice or virtue. They argue that, because violence is necessarily wrapped up with hierarchical and exclusive structures and imaginaries, legitimising it in terms of the ends that it serves, or how it is perpetrated, no longer makes sense.